2007
DOI: 10.1007/s00210-007-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine inhibits muscarinic type 3 receptors expressed in Xenopus oocytes and muscarine-induced intracellular Ca2+ elevation in cultured rat dorsal root ganglia cells

Abstract: Dexmedetomidine, an alpha(2)-adrenoceptor agonist, has been approved for clinical use, although the mechanism of dexmedetomidine action has not been fully elucidated. Several studies have shown that G protein-coupled receptors (GPCRs) are recognized as targets for anesthetics and analgesics. Therefore, it is of interest to determine whether dexmedetomidine affects the function of GPCRs other than the alpha(2)-adrenoceptor. We examined the effects of dexmedetomidine on M(1), M(3), 5-HT(2C), substance P, and ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…In addition to its effectiveness in sedation, DEX reportedly has a regulatory effect on VGCC and oxidative stress in neurons202122. Excessive production of mitochondrial ROS and an overload of Ca 2+ through increased TRPM2 and TRPV1 channel activity are two of the main causes of neurodegenerative diseases in hippocampus and induction of peripheral pain in DRG (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its effectiveness in sedation, DEX reportedly has a regulatory effect on VGCC and oxidative stress in neurons202122. Excessive production of mitochondrial ROS and an overload of Ca 2+ through increased TRPM2 and TRPV1 channel activity are two of the main causes of neurodegenerative diseases in hippocampus and induction of peripheral pain in DRG (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The results of recent studies show that DEX decreased cerebral ischemia and SCI-induced intracellular ROS production and apoptosis in the brain and DRG of rat, respectively119. Recently, it has been demonstrated that DEX potently inhibits overload Ca 2+ entry through voltage gated calcium channels (VGCC) and glutamate (NMDA) receptors in the DRGs and hippocampus of rats202122. Therefore, DEX may reduce the entry of overload Ca 2+ via modulation of TRPM2 and TRPV1 channel activations in the HIPPO and DRG neurons of rats with cerebral ischemia, and this effect should be clarified.…”
mentioning
confidence: 99%
“…The exact mechanism that mediates dexmedetomidine analgesia is still unknown. However, previous studies have found that dexmedetomidine inhibits elevations in intracellular Ca 2+ levels in cultured rat dorsal root ganglia cells by its α 2 -adrenoceptor agonist effect [53]. Taken together, these observations suggest that dexmedetomidine may decrease postsynaptic intracellular Ca 2+ concentrations by acting at presynaptic α 2 -adrenoceptors, thereby affecting the expression of P2X7R and ERK phosphorylation.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, we also demonstrated that systemic ATRO attenuates the antinociceptive effect of DEX. In cultured rat dorsal root ganglia cells, DEX also inhibits muscarinic type 3 receptors and muscarine-induced intracellular Ca 2+ elevation [43]. Moreover, cholinergic pain modulation may also involve first-order neurons (sensory neurons responsible for delivering sensory information to the central nervous system) via muscarinic acetylcholine M2 receptors.…”
Section: Discussionmentioning
confidence: 99%